Intertekstual Novel Ma Yan Karya Sanie B. Kuncoro dan Novel Selembar Itu Berarti Karya Suryaman Ampriono Kajian Sastra Bandingan - Endang Wahyuningsi; Rico Aprisa; Putri Wahyuli (Departement of Mathematics Education, 2023)
The problem discussed in this study is the comparison of the Mayan character in the novel Ma Yan by Sanie B. Kuncoro and the character Putri in the novel Selembar Itu Berarti by Suryaman Ampriono in the way the figures maintain education in the midst of the poverty line and the economic crush from the social aspect. The way the characters maintain education in the midst of the poverty line and economic hardship is compared through the social aspects of each character. This type of research is literaty research using the hermeneutic method. The data collection technique used is the data card technique which is carried out through reading the novel carefully, understanding the content of the novel, and recording data evidence in the novel. The research data that has been collected is then analyzed by identifying data on how the characters maintain education in the middle of the poverty line from the social aspect to Mayan and Putri figures, data classification and data interpretation. From the results of the study found a comparison of how the characters maintain education in the middle of the poverty line which is seen from the social aspect. Sosial aspect in maintaining education in the form of economic conditions, moral values, and social relations.